Human liver spheroid cultures in microfluidic chip co-cultures and comparative MetID studies - Asserlind, Johanna (My University, 2017)
The liver is the most important site of drug metabolism in the human body. During drug development, it is therefore of high importance to employ a robust in vitro model that resembles the in vivo microenvironment, and is able to accurately predict the metabolism and disposition of compounds. This thesis is divided into two major parts. First, the metabolism of a set of compounds was characterized qualitatively in spheroids made from primary human hepatocytes (PHH), and the resulting data was compared to previous data from hepatocyte suspension culture and human in vivo data. The metabolites formed during a 72 hour incubation period was analyzed by LC-MS. Second, a co-culture between human liver spheroids, made from HepaRG cells and primary hepatic stellate cells, and primary human pancreatic islets in microfluidic 2-organ-chips was established, and the liver spheroids were functionally characterized. A total of 5 chip experiments were performed, where each chip experiment lasted for 7 days, and different conditions such as medium composition where examined. Various staining techniques and measurements of secreted albumin and LDH were used to assess long-term sustainability, function and viability of the spheroids. Some of the metabolites seen in humans were also formed in PHH spheroids, but the spheroid model was not able to fully predict the human in vivo metabolism. Spheroids were not shown to be a significantly better model to use compared to suspension cultures during these experiments. CYP activity analysis showed that decreasing metabolic function after a change in medium composition might be a factor. HepaRG spheroids were able to display several liver-like functions when cultured in the multi-organ chips, but the large size of the spheroids led to the formation of necrotic cores. Overall, while certain parameters need to be improved, the liver spheroids are promising models for studying several different aspects of liver functions as well as for establishing organ system models.
Keywords: Building Futures; Energi; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Annan humaniora; Building Futures; Energy; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Other Humanities